2013
DOI: 10.1021/ja4107034
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Selective C–H Functionalization Using a Nitrile-Based Directing Group and Cleavable Si-Tether

Abstract: A nitrile-based template that enables meta-selective C-H bond functionalization was developed. The template is applicable to a range of substituted arenes and tolerates a variety of functional groups. The directing group uses a silicon atom for attachment allowing for a facile introduction/deprotection strategy increasing the synthetic practicality of this template.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
81
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(86 citation statements)
references
References 66 publications
0
81
0
5
Order By: Relevance
“…[24] Besides their easy synthesis as well as facile removal, the elongated SiÀCa nd SiÀOb onds permitted an optimal separation between the directing nitrile group and the aromatic reactant. [24] Besides their easy synthesis as well as facile removal, the elongated SiÀCa nd SiÀOb onds permitted an optimal separation between the directing nitrile group and the aromatic reactant.…”
Section: Silyl-bridged Directing Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…[24] Besides their easy synthesis as well as facile removal, the elongated SiÀCa nd SiÀOb onds permitted an optimal separation between the directing nitrile group and the aromatic reactant. [24] Besides their easy synthesis as well as facile removal, the elongated SiÀCa nd SiÀOb onds permitted an optimal separation between the directing nitrile group and the aromatic reactant.…”
Section: Silyl-bridged Directing Groupsmentioning
confidence: 99%
“…[33] With the help of as imilar 2-cyanophenol-derivatized template,t hey were able to achieve ah ighly regioselective meta-olefination of arange of aryl alcohols from adistal location of the directing group.I nt he presence of Pd(OAc) 2 as the catalyst, aw ide range of aryl alcohols,namely 3-phenylpropanols,2-phenoxyethanols,a nd 2-(phenylamino)ethanols,w ere succesfully olefinated at the meta-position with yields as high as 91 % (meta/others > 20:1; 86 a-g). [9,24] As will be discussed in the following sections,Y ua nd co-workers achieved the metaolefination of 2-phenylethyl alcohols by using aheterocyclicbased template. [11] Further theoretical calculations showed that the C-N-Ag angle played an important role in scaffolds with short linkers,w hereas the torsional strain resulting from the gauche conformation about the phenylethyl bond is crucial for longer linkers to obtain metaselectivity.Furthermore,the directing group can be removed by treatment with ceric ammonium nitrate (CAN) at room temperature (87!88).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Transformations reported by Hartwig, [7] Yu, [8] Tan, [9] Dong, [10] Zhao, [11] and us [12] demonstrated the feasibility of this concept in C–H functionalization. Specifically, a recent report from Zhao and coworkers [11b] demonstrated the Pd-catalyzed ortho -selective arylation to construct biaryls, using oximes as the surrogate species.…”
mentioning
confidence: 89%
“…The groups of Tan 34 and Maiti 35 have independently developed the type-2 nitrile-based silyl DGs ( 22 and 23 , Scheme 2) for meta - and para -C–H functionalization of arenes, respectively, by merging Yu’s nitrile-based DG for a remote C–H functionalization 36 with our temporary silyl DG concept (Scheme 32). Both works feature a broad substrate scope, high degrees of regioselectivity, and the possibility to recover and reuse the silyl DG.…”
Section: C(sp2)–h Functionalization Via Silicon Tethersmentioning
confidence: 99%